Drug-induced heart failure: a real-world pharmacovigilance study using the FDA adverse event reporting system database - Huang, Youqi; Chen, Xiaowen; Chen, Mingyu; Lin, Yuze; Chen, Bingqi; Gao, Hongjin; Chen, Min (Frontiers in Pharmacology, 2025)
ObjectiveAlthough there are certain drug categories associated with heart failure (HF), most of the associated risks are unclear. We investigated the top drugs associated with HF and acute HF (AHF) reported in the FDA Adverse Event Reporting System (FAERS).MethodsWe reviewed publicly available FAERS databases from 2004 to 2023. Using the search terms “cardiac failure” or “cardiac failure acute” and classifying cases by drug name, we processed and analyzed drug reports related to HF or AHF.ResultsFrom 2004 to 2023, 17,379,609 adverse drug events were reported by FAERS, of which 240,050 (1.38%) were reported as HF. Among those with HF, the male-to-female ratio was 0.94% and 52.37% were >65 years old; 46.2% were from the United States. There were 5,971 patients with AHF. We identified 38 drugs and 13 drug classes with a potential high risk of causing HF, and 41 drugs and 19 drug classes were associated with AHF. The median onset times of HF and AHF were 83 days (IQR: 11–416) and 49 days (IQR: 8–259), respectively. The Weibull shape parameter (WSP) test showed early failure-type profile characteristics.ConclusionThis study highlights key drugs associated with drug-induced HF and AHF, emphasizing the importance of early risk assessment and close monitoring, particularly during the initial stages of treatment. These findings contribute to a better understanding of drug-induced HF and provide a basis for future research on its underlying mechanisms.